High velocity impact perforation on C/C-SiC composites - Srivastava V.K.; Maile K.; Klenk A. (My University, 2025)
High velocity impact tests were performed with a Split-Hopkinson pressure bar to achieve post-cracking of oxidised (1600 °C for 10 min) and unoxidised C/C-SiC composites. Weak and strong bond C/C-SiC composites delivered by different manufacturers were used for the impact perforation tests. Different states of impact damage were conducted on each type of sample by variation of pressure and velocity. Composite specimens were evaluated by the nondestructive testing method of the DC potential drop technique before and after the impact damage to quantify the damage. The changes in flexural strength of each sample were measured to observe the relationship with the impact energy and DC potential drop values. The results show that the change in flexural strength decreases with increase of impact energy, but impact energy and change in flexural strength increased with the increase of the DC potential drop value, which confirm that the electric resistance of composites decreased with the presence of post-damage under high velocity impact.